Determinants of Corporate Social Disclosures in Kenya: A Longitudinal Study of Firms Listed on the Nairobi Securities Exchange - Wachira, Muturi (European Scientific Journal, ESJ, 2017)
This study which was exploratory in nature aimed to examine the extent to which firms listed on the Nairobi Securities Exchange disclosure social responsibility information and also to determine company and corporate governance variables that influence the Corporate Social Disclosures (CSD) practice in Kenya. Data on the disclosure index and company characteristics were obtained from the annual reports of the respective companies. A relationship between the disclosure index and the various company characteristics was determined. It was found that size, profitability, liquidity, industry in which a company operates have a positive influence on the level of CSD. In addition, a company that a dispersed ownership disclosed more information than a company with concentrated ownership. Gearing and country of origin were found to have no influence on the level of CSD.